Meeting Summary: A 2017 View of Active Galactic Nuclei - Netzer, Hagai (Frontiers in Astronomy and Space Sciences, 2018)
The topics covered in this summary review reflect the major areas discussed in the Padova meeting, in April 2017. They are divided into general categories: those areas where large progress has been made leading to a real new understanding (what we are doing “right”), and those where we are still in the dark (what we are doing “wrong”). The division reflects the status of the field as well as my subjective opinion.